2020
DOI: 10.3389/fpubh.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mental Health Tools for Caregivers of Older Adults—A Scoping Review

Abstract: Informal caregivers have an important role in bridging the gap between the assistance care recipients need and what can be provided by the health care systems across Europe. The burden of the caregiving role places a significant threat to caregiver health, and the vast majority of caregiver's report stress and emotional strain, depression, and increased rates of chronic diseases. In line with this, strengthening the caregiver's mental health is one of the main goals for optimal caregiving. Caregivers already s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…Autonomous systems such as social robots can support care recipients in a variety of ways but also support their caregivers' physical and mental health (see ref. [22]). Moreover, social robots are increasingly being built equipped with technologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous systems such as social robots can support care recipients in a variety of ways but also support their caregivers' physical and mental health (see ref. [22]). Moreover, social robots are increasingly being built equipped with technologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, depression in caregivers of those with VI is highly prevalent due to the burden of care associated with the role, 24,25 and should be addressed. In previous studies, interventions providing emotional support elements have shown a decrease in depressive symptoms 61 . Although this module can be completed by both the person with VI and their carer, it was recommended that certain elements be adapted to cater for the individual group’s emotional needs, with specific scenarios of when and how some of the suggested techniques can be used.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual ideals reaching agreement in survey 1 were categorised into seven intervention sections based on structures used by previous psychosocial intervention for people with VI 60–63 as follows: (i) understanding VI, (ii) addressing emotional wellbeing, (iii) suggestions for functional wellbeing, (iv) improving physical wellbeing, (v) enhancing social wellbeing, (vi) addressing carers’ wellbeing and (vii) maintaining wellbeing in the long term after completing the intervention ( Figure ). For each section, two to four modules were suggested to address this aspect of wellbeing as seen in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Digital interventions for caregivers, delivered via mobile apps, web-based and VR, promote building skills, emotionself regulation, education, information about the caregiving role and provide skill training (Petrovic and Gaggioli, 2020). Examples of successful adaptation of psychotherapeutic techniques into digital interventions delivered across platforms include RX Refill, Care, Care4Caregivers, CareHeroes, Mindfulness-Based Stress Reduction (MBSR), UnderstandAid, Webnovela Mirela, Aging Service Technology (AST) and a VR intervention Through D'mentia Lens (Petrovic and Gaggioli, 2020).…”
Section: Psychological Interventions To Reduce Caregiver's Burdenmentioning
confidence: 99%